Synthesis and Performance of a New Surfactant for Enhanced Oil Recovery - Elraies,, K.A (2009)
Due to the high cost of surfactant production caused by petrochemical feedstocks, considerable attention has been given to non-edible vegetable oils as an alternative source of feedstock. In this paper, a new non-edible oil derived surfactant based on Jatropha plant is synthesized. A single step route was used for synthesizing epoxidized methyl ester sulfonate (EMES) for enhanced oil recovery application. The performance of the resultant surfactant was studied by measuring the interfacial tension between the surfactant solution and crude oil, and its thermal stability at reservoir temperature. The EMES showed properties similar to sodium dodecyl sulfate, such as the reduction of interfacial tension to 3.45 mN/m. The advantage of the newly EMES is the low cost of production that makes it a promising surfactant for enhanced oil recovery application and other uses.